2020
DOI: 10.1534/genetics.120.303137
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Classifying Shared Selective Sweeps from Multilocus Data

Abstract: Positive selection causes beneficial alleles to rise to high frequency, resulting in a selective sweep of the diversity surrounding the selected sites. Accordingly, the signature of a selective sweep in an ancestral population may still remain in its descendants. Identifying signatures of selection in the ancestor that are shared among its descendants is important to contextualize the timing of a sweep, but few methods exist for this purpose. We introduce the statistic SS-H12, which can identify genomic region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 140 publications
2
17
0
Order By: Relevance
“…Whereas haplotypes are character strings indicating the state of a biallelic SNP as either reference or alternate along a region of one copy of an individual’s genome, MLGs have three possible states for each biallelic SNP—homozygous reference, homozygous alternate, or heterozygous—and half the sample size of phased haplotypes. We found that, as with the transition between phased and unphased data for haplotype homozygosity statistics ( Harris et al 2018 ; Harris and DeGiorgio 2020 ), trends in power for the unphased application of the T statistic were wholly consistent with those of the phased application, for both hard and soft sweeps ( supplementary fig. S15 , Supplementary Material online).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Whereas haplotypes are character strings indicating the state of a biallelic SNP as either reference or alternate along a region of one copy of an individual’s genome, MLGs have three possible states for each biallelic SNP—homozygous reference, homozygous alternate, or heterozygous—and half the sample size of phased haplotypes. We found that, as with the transition between phased and unphased data for haplotype homozygosity statistics ( Harris et al 2018 ; Harris and DeGiorgio 2020 ), trends in power for the unphased application of the T statistic were wholly consistent with those of the phased application, for both hard and soft sweeps ( supplementary fig. S15 , Supplementary Material online).…”
Section: Resultssupporting
confidence: 54%
“…2011 ; Kern and Schrider 2018 ; Mughal and DeGiorgio 2019 ), or drawing inferences from a posterior distribution by approximate Bayesian computation ( Garud et al. 2015 ; Harris et al 2018 ; Harris and DeGiorgio 2020 ). We demonstrate with simulated data that the T statistic identifies recent hard and soft sweeps and performs especially well for population size expansion models.…”
Section: Introductionmentioning
confidence: 99%
“… 99 ), and SS- H 12 (ref. 100 )) summary statistics for each subwindow. All summary statistics were normalized by dividing each statistic by its sum across all subwindows.…”
Section: Methodsmentioning
confidence: 99%
“…These methods employ both model-free approaches based on allele frequencies, which can detect shared ancestral selection between a set of populations since they diverged from a closely related outgroup ( Figure 4 B) (ancestral branch statistic (ABS) [ 39 ], the similar levels of exclusively shared differences (LSD) method [ 40 , 41 ], and the model-based 3P-CLR [ 42 ]). A wealth of additional approaches also exist for detecting shared ancestral selection events [ 43 , 44 , 45 , 46 , 47 ]. This collection of methods could potentially be utilized to test ancestral selection in ancient and living indigenous populations that share coastal environments and marine sustenance strategies.…”
Section: Methods For Detecting Positive Selectionmentioning
confidence: 99%
“…New methods are also available that directly compare populations without the need of an outgroup. One such approach is SS-H12 [ 47 ], which employs haplotype data. This method has great power to detect shared positive selection events, and excellent accuracy at distinguishing between events that occurred prior to population splits (ancestral selection) and independently in each population after their split (convergent selection).…”
Section: Methods For Detecting Positive Selectionmentioning
confidence: 99%